Jesse Stone. Lost in paradise - Harmon, Robert; Brandman, Steven; Selleck, Tom, 1945-; Brandman, Michael; Sudduth, Kohl; Reuben, Gloria, 1964-; Hope, Leslie; Parker, Robert B., 1932-2010.; Brandman Productions, Inc.; TWS Productions II, Inc.; Sony Pictures Home Entertainment (Firm) (Culver City, California : Sony Pictures Home Entertainment, 2016)
Jesse investigates the grim works of a serial killer in Boston and becomes concerned with a wayward teen in Paradise.
"Based upon characters created in Robert B. Parker's Jesse Stone books."
Originally produced in 2015.
Anamorphic widescreen (1.78;1).
Tom Selleck, Kohl Sudduth, Gloria Reuben, Leslie Hope, William Sadler, Amelia Rose Blaire, Alex Carter.
MPAA rating: Not rated CHV rating: PG OFRB rating: G.
DVD ; region 1 ; widescreen ; Dolby digital 5.1.
Keywords: Stone, Jesse -- (Fictitious character) -- Fiction; Serial murderers -- Massachusetts -- Boston -- Drama; Criminal investigation -- Massachusetts -- Boston -- Fiction; Police chiefs -- Fiction -- Massachusetts -- Boston; Made-for-TV movies; Police films; Crime films; Video recordings for the hearing impaired; Feature films